Effect of Learning Culture on Organizational Commitment in IT Industry - MONICA, BENITA. S.; SRILEKHA (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the study is to understand the relationship between learning culture and organisational commitment in IT industry. The learning culture of the organisation is measured under several dimensions namely, continuous learning, dialogue & inquiry, team learning & collaboration, embedded systems, empowerment, systems connection and strategic leadership. The organisational commitment is studied in three aspects such as affective commitment, continuance commitment and normative commitment. The sample was 104 employees who are working in IT industry. The organizational commitment was used to detect the effects of learning culture in IT industry among employees. The results proved that the dimensions of learning organisation have positive effect on organisational commitment. Continuous learning did not have any effect over commitment.